Government Spending Efficiency on Economic Growth: Roles of Value-added Tax. Issue 2 (3rd April 2017) - Chan, Sok-Gee; Ramly, Zulkufly; Karim, Mohd Zaini Abd
Abstract: This study examines the impact of government spending efficiency on the economic growth of 115 countries with value-added tax (VAT) system. We seek to examine the moderating role of the VAT system on the relationship between public spending efficiency and the economic growth. Using Generalized Method of Moments estimation based on two-step estimate, we found (1) government spending efficiency promotes economic growth, (2) the VAT system is found to enhance the effect of an efficient government spending on the economic growth and (3) the moderating role of the VAT system is further enhanced by quality of democracy and legislative strength of the government.